And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Keywords: BATES, Robert H., 1942-; EVANS, Peter, 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation, The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)